CircRNA: the potential biomarkers and therapeutic targets in oral squamous cell carcinoma (OSCC) - Lv, Jun-Lin; Ma, Ru; Ren, Yu-Shan; Liang, Qing-Yue; Zhang, He-Meng; Dong, Gui-Cheng; Li, Jie (Frontiers in Oncology, 2025)
Circular RNAs (circRNAs) are a new category of non-coding RNAs implicated in the molecular pathology of cancer, such as oral squamous cell carcinoma (OSCC). Circular intronic RNAs (ciRNAs), exonic circRNAs (ecircRNAs), and exon-intron circRNAs (EIciRNAs) are three primary types of circRNAs resulted from the circularization of extron and intron which give rise to the distinct biology of circRNAs. Due to their unique structure and biogenesis, circRNAs exhibit tissue- and cell-specific expression profiles. Recent studies have highlighted that in OSCC, some circRNAs are differentially expressed compared with adjacent normal tissues, with these variables potentially influencing OSCC initiation and progression through diverse mechanisms. Furthermore, earlier clinical trials have indicated that circRNAs could be considered as potential therapeutic targets and biomarkers for OSCC. It should be noted that many circRNAs modulate tumor cells proliferation/apoptosis and metastasis via regulating gene transcription and post transcriptional expressions. Furthermore, certain circRNAs function as effective microRNA sponges, thereby inhibiting oncogenic pathways in OSCC. In summary, the discovery of circRNAs has unveiled new avenues for cancer research, particularly in OSCC. This review provides an overview of circRNA biogenesis, their biological functions, and their roles as differentially expressed molecules in OSCC, emphasizing their potential for clinical application and warranting further investigation into their functional and therapeutic relevance.